Learning to use music as a resource: the experiences of people with dementia and their family care partners participating in a home-based skill-sharing music intervention: a HOMESIDE sub-study - McMahon, Kate; McFerran, Katrina; Clark, Imogen N.; Odell-Miller, Helen; Stensæth, Karette; Tamplin, Jeanette; Baker, Felicity A. (Frontiers in Medicine, 2023)
An increasing number of people with dementia receive informal care from family members to help them remain living in the community. Music therapy is particularly beneficial for supporting the wellbeing of people living with dementia. However, little is known about how music therapy might support people with dementia and their family care partners as dyads. This study explored the experiences of six dyads participating in a 12-week home-based skill-sharing music intervention facilitated by a music therapist. We examined their experiences during the intervention period and in the 3-6 months following. This study was conducted within a larger randomised control trial, HOMESIDE. Data was collected through video-recorded music-based interviews, participant diaries, and a semi-structured interview. Data was analysed using an abductive and relational-centred research approach in consideration of the Contextual Connection Model of Health Musicking for People Living with Dementia and their Family Care Partners. The study found fifteen themes that describe dyads’ supported experiences of sharing music in their homes. These were organised into three global themes: 1) Experiences were shaped by complex influences; 2) A connected musical ecosystem; and 3) Music was a resource for wellbeing. This study highlighted the important role of personalised facilitation and the therapeutic relationship as dyads learned to use music as a resource through a process of trial and error. The implications for skill-sharing, indirect music therapy and direct music therapy practice are discussed.